Pembentukan satgas duta anti-bullying untuk pencegahan perilaku bullying di MTs X - Putri Wulandari; Uun Zulfiana (Procedia : Studi Kasus dan Intervensi Psikologi, 2026)
Bullying remains a prominent problem in one of the Islamic Junior High Schools (MTs) in Malang Regency, particularly in verbal forms such as physical abuse and the use of parents’ names as a source of verbal bullying. Previous efforts to address this issue tended to be reactive when cases already occurred and did not involve a community approach. This study aims to develop an Anti-bullying Ambassador Task Force as an agent of change to foster a bullying-free school culture. The study subjects involved 24 students aged 12–16 who were screened according to criteria. Assessments were conducted through interviews, observations, and psychological tests. The results showed an increase in students’ understanding of bullying and their readiness to handle problems. These findings suggest that the Anti-bullying Ambassador Task Force program can improve prevention efforts and create a safer school environment.